UNDER THE LENS OF TIME: THE CULTURE OF SPORT IN THE POSTMODERN ERA: THE CULTURE OF SPORT IN THE POSTMODERN ERA - Nedeljković, Zoran D. (Political Review, 2025)
In this study, the author, drawing on relevant literature and employing a comparative-historical method, analyzes sporting events across different cultural and historical periods. The text  examines the relationship between sport, culture, and time in the context of the postmodern era, with particular emphasis on distinguishing physical, social, and technological time.It is shown that in the era of global technological acceleration, sport has become a mirror of contemporary society, which evaluates individuals based on records, results, and media exposure, rather than the virtue and spirit of the game advocated by the ancient Greek Olympians. Unlike them, the modern athlete becomes a media hero and a magnet for the global entertainment industry, representing    a continuation of the Roman circus tradition in a postmodern form. Drawing on  Spengler’s  theory  of the cycles of culture and civilization, the author demonstrates that modern (mass) man, from the industrial age to the present, has lost a sense of historical duration, living in ahistorical time, trapped in the “cage” of the present moment. This phenomenon is also reflected in sport, which increasingly loses  its original meaning. Technological progress and media spectacularization condition the gradual disappearance of sport’s humanistic dimension.
Keywords: sport; culture; postmodernism; time; technological time; globalization; media; record; athletics; Olympic Games